1991
DOI: 10.1111/j.1540-6261.1991.tb04645.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stock Markets with Multiple Assets: An Experimental Analysis

Abstract: We study the performance of the rational expectations hypothesis in multiperiod experimental markets with multiple assets. We find that the markets are generally inefficient from the point of view of full information aggregation. However, arbitrage relationships hold, and it is not possible to detect the informational inefficiency by using some standard tests of market efficiency. These findings suggest that the lack of arbitrage opportunities and the failure of common tests to reject inefficiency are not suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…7 See the surveys in Cadsby and Maynes (1998) and Sunder (1995). Srivastava (1991) replicate portfolios of options, stocks, and cash in a multipleasset experimental market with two stages and information asymmetry. The authors show that if the information asymmetry cannot be resolved, price discrepancies frequently persist.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…7 See the surveys in Cadsby and Maynes (1998) and Sunder (1995). Srivastava (1991) replicate portfolios of options, stocks, and cash in a multipleasset experimental market with two stages and information asymmetry. The authors show that if the information asymmetry cannot be resolved, price discrepancies frequently persist.…”
Section: A Literature Reviewmentioning
confidence: 99%
“…Prior experimental market studies mostly focus on the market's ability to aggregate information. Studies have shown that markets can disseminate private information (Plott and Sunder [1982]) and aggregate diverse private information under certain conditions (Plott and Sunder [1988], Lundholm [1991], O'Brien andSrivastava [1991]). In prior experiments, dividends are exogenously specified.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the available empirical literature provides mixed evidences on the applicability of RWH in security markets. Some studies support it (Godfrey et al, 1964;Fama, 1965;Fama, 1970;Fama, 1991;Alford & Guffey, 1996;Dow & Gorton, 1997;Barkoulas & Baum, 1997), and many others refute it (Grossman & Stiglitz, 1980;Shiller & Perron, 1985;Lo & MacKinlay, 1988;O'Brien & Srivastava, 1991;Barkoulas & Baum, 1996;Peress, 2010;Latif et al, 2011;Patel et al, 2012;Immonen, 2015). The rejection of the RWH infers existence of dependence and predictability in security returns.…”
Section: Persistence In Financial Asset Marketsmentioning
confidence: 99%